Representation of Raden Saleh’s Painting the Arrest of Prince Diponegoro in Interactive Digital Educational Media - JESSIKA OKTAVIA (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2025)
Raden Saleh’s painting The Arrest of Prince Diponegoro is one of the most significant works in Indonesian art history, valued not only for its aesthetic qualities but also for its symbolic resistance to colonialism. This study aims to examine how the cultural and historical values embedded in the painting can be re-presented through interactive digital education in the form of a game. The research employed a qualitative method through literature review, visual observation, and interviews with art practitioners and digital media users. The findings reveal that interactive media enables artworks to be experienced not merely as static visuals but through participatory mechanisms such as exploration, object interaction, and digital narratives. Therefore, digital adaptation through gaming can serve as an educational tool aligned with technological development while enhancing public appreciation of Indonesian art and history.